Hypromellose in Ophthalmology - O. I. Butranova; S. K. Zyryanov (Oftalʹmologiâ, 2023)
Dosage forms for topical ocular administration are the basis of patient management in ophthalmology. The eye is a structure evolutionarily protected from the effects of xenobiotics by a number of physiological and anatomical barriers. The development of dosage forms, the targeted delivery into the eye structures is carried out due to the inclusion of special excipients, is aimed at improving the efficiency of managing patients with eye diseases. The action mechanisms of the most common groups of excipients used in ophthalmology underlie their effectiveness and safety, as well as create a basis for the various dosage forms development. Cellulose derivatives, due to their physicochemical and pharmacological characteristics, are one of the preferred groups for the development of topical dosage forms used in ophthalmology. Hypromellose (hydroxypropyl methylcellulose) is one of the most studied cellulose derivatives, which is characterized by a wide range of indications for both the active substance (artificial tear component) and the excipient. The favorable pharmacological properties of hypromellose (the ability to provide long-term exposure to effective concentrations of drugs used topically in ophthalmology, the ability to increase the degree of hydration of the cornea) contribute to the active study of this substance to assess the possibilities of its use in the development of new dosage forms (nanoparticles), as well as expanding the existing list of indications. This review is devoted to the analysis of clinical and experimental studies of the efficacy and safety of hypromellose.